Discourses in Teachers' Talk about Writing. (October 2019) - Sturk, Erika; Lindgren, Eva
Views about what writing is and how it should be taught have varied over the years as well as across contexts. Studies of curricula, teaching materials, and teaching practices have shown a strong focus on skills, genres, and processes, but few have asked teachers about their perspectives on writing. In this article we explore what views, or discourses, of writing are currently active among teachers in Swedish compulsory education, covering ages from 7 to 15. Sixty teachers answered a questionnaire with open and closed questions. Using Ivanič's framework for discourses of writing, the answers were analyzed holistically in order to define what main discourse, or discourses, each teacher represented. Results show that most teachers represent one main discourse, but that a combination of discourses occur, in particular among teachers from the earliest school years (1–3). The most common discourse was the process discourse, followed by genre, creativity, skills, and thinking. None of the teachers represented the social practice or the sociopolitical discourse. The results concur with findings from studies of curricula, teaching materials, and teaching practices both in Sweden and globally and are discussed in relation to what literacy skills may be necessary in the 21st century in order to participate in social and political life.